269 Differentiating vaccine reactions from invasive bacterial infections in infants presenting to the emergency department in the 4CMenB era: a retrospective descriptive comparison. (17th August 2022) - Channon-Wells, Samuel; Tough, Emily; So, Neda; O'Connor, Daniel; Snape, Matthew
Abstract : Aims: Since the introduction of the capsular group B Meningococcal vaccine (4CMenB) into the routine UK immunisation schedule in 2015 there has been an increase in children with transient Adverse Events Following Immunisation (AEFI) such as fever and irritability presenting to primary care and the Emergency Department (ED). We aimed to determine if clinical or laboratory features on presentation can differentiate infants with AEFI from those with Invasive Bacterial Infection (IBI). Methods: During a service evaluation and improvement project we conducted a retrospective descriptive study of infants with IBI, Urinary Tract Infection (UTI) or AEFI from two previously published cohorts. Children with AEFI or UTI were identified by reviewing all discharge summaries of infants presenting to ED in Oxfordshire, UK, between 2011-2018 (spanning the introduction of 4CMenB). Patients were classified as either 'probable-AEFI' (symptoms <48-hours after immunisation, no alternative focus found), 'possible-AEFI' (symptoms <48-hours, possible alternative focus) or UTI by two clinicians independently. Children with IBI were identified from all positive blood and cerebrospinal fluid (CSF) cultures in children 7-weeks to 8-months of age. We compared presenting clinical symptoms, including National Institute for Health and Care Excellence (NICE) 'traffic-light' risk of severe illness, and laboratory test results. To enable comparison with the post immunisation inflammatory response in infants not requiring medical evaluation, we also included blood results taken at 24-hours post-immunisation from 4-month-old infants enrolled in the EUCLIDS 4CMenB study. Results: The study included 192 infants: 97 with probable-AEFI, 25 possible-AEFI, 44 IBI & 27 UTI. 95% with IBI had blood tests (FBC and CRP), compared with 28% probable-AEFI, 48% possible-AEFI and 42% UTI. Blood tests from 21 EUCLIDS participants were available. CRP was the only blood marker significantly different between IBI and probable-AEFI (p=0.028, figure 1 ). CRP at presentation had AUC of 0.66 (95% CI: 0.52–0.80) for predicting IBI, with a CRP value >55.5mg/L differentiating IBI from AEFI with high specificity (100%) but low sensitivity (49%). However, CRP was not statistically different between IBI and AEFI when restricted to children after 4CMenB introduction. Positive urine leucocytes and nitrites were both significantly more common with IBI than AEFI ( table 1 ). Irritability, rash, vomiting, diarrhoea, and rigors were all significantly more common in IBI than probable-AEFI. Traffic-light classification as 'High' or 'Low' risk was strongly predictive of outcome, with odds ratios of 4.02 (1.61–10.32) and 0.15 (0.04–0.43) for high- and low-risk respectively. However, 5 cases of IBI were mis-classified as low-risk on initial presentation. Intermediate-risk classification did not predict outcome. Seizures and fever were not statistically different between groups. Inflammatory markers in 'well' infants 24-hours after immunisation were significantly raised, and either the same or higher than infants with probable AEFI. Conclusion: Clinical features on presentation may aid risk stratification but cannot reliably differentiate IBI from AEFI in infants presenting to the emergency department. Blood results are generally unhelpful due to post-vaccination inflammatory responses, although CRP >55.5mg/L is highly suggestive of IBI. Improved biomarkers and clinical prediction tools are required to aid management in febrile infants post-vaccination.